Changes in the energy metabolism of the gills of Litopenaeus vannamei under carbonate alkalinity stress and recovery conditions - Xiao, Meng; Nan, Yuxiu; Li, Jitao; Wang, Yun; Zhu, Ruijie; Duan, Yafei (Frontiers in Marine Science, 2025)
In saline-alkaline water, carbonate alkalinity (CA) stands as the predominant detrimental environmental element impacting aquatic fauna. As a multifunctional organ, the gill plays a key role in the regulation of energy metabolism in shrimp. In this study, the low-salinity cultured Litopenaeus vannamei was exposed to CA stress for a period of 7 days, and then the stress was relieved and recovered for 7 days. The study examined the alterations in the gill energy metabolism following exposure to CA stress and subsequent recovery, analyzing these changes through different biological functional aspects. The results demonstrated that CA stress led to alterations in the gill histomorphology and disrupted the balance of energy metabolism-related parameters. In detail, after CA stress, carbohydrate metabolism related indexes, the pyruvate (PYR) content showed increases, as did the relative expression of the hk, pk, and pdh genes, while the glucose (GLU) and lactate (LAC) content and the expression of the idh gene were slightly decreased; lipid metabolism related indexes, such as the triglycerides (TG) content and the expression of the ampk gene were slightly increased, and the expressions of the srebp, acc, and fas genes were increased significantly; tricarboxylic acid (TCA) cycle related indexes, such as the expressions of the cs, odh, and sdh genes were up-regulated, whereas the expressions of the mdh and idh genes were significantly down-regulated, the expression of the fh gene was slightly decreased in regulation; electron transfer chain related indexes, such as the expressions of the ndh, cytc, coi, cco, and atph genes were significantly increased. Collectively, these alterations jointly affected the energy metabolism homeostasis. After the CA stress was relieved, while certain physiological parameters demonstrated improvement, they did not completely revert to the levels seen in the control group. The findings indicated that CA stress exerted an adverse effect on the histomorphology and energy metabolism in the gills of shrimp, likely by disrupting the functions of glycolysis, lipid metabolism, TCA cycle, and electron transport chain, which may further affect the growth and survival of the shrimp.